Réponses

  • Utilisateur Brainly
2014-03-07T14:39:51+01:00
D= (12x+3)(2x-7)- (2x-7)^{2}

1°developper et reduire D

D= (12x+3)(2x-7)- (2x-7)²
=24x²+6x-84x-21-(4x²-28x+49)
=24x²-78x-21-4x²+28x-49
=20x²-50x-70

2°factiriser D

D= (12x+3)(2x-7)- (2x-7)²
=3(4x+1)(2x-7)-(2x-7)(2x-7)
=(2x-7)(12x+3-2x+7)
=(2x-7)(10x+10)
=10(2x-7)(x+1)


Meilleure réponse !
  • Utilisateur Brainly
2014-03-07T14:40:05+01:00
Développement:

D= (12x + 3) (2x - 7) - (2x - 7)²
D= 24x² - 84x + 6x -21 - (4x² -28x +49)
D= 24x² - 78x -21 -4x² +28x -49
D= 20x² -50x -70

Factorisation:

D= (12x + 3) (2x - 7) - (2x - 7)²
D= (2x - 7) (12x + 3 -2x +7)
D= (2x - 7) (10x + 10) 

Voilà ! J'espère t'avoir aidé(e) ! :)